Affect Dysregulation in Context: Implications and Future Directions of Experience Sampling Research on Affect Regulation Models of Loss of Control Eating - Mikhail, Megan E. (Frontiers in Psychiatry, 2021)
Loss of control eating is a core, transdiagnostic eating disorder symptom associated with psychological distress, functional impairment, and reduced quality of life. However, the factors that contribute to persistent loss of control eating despite negative consequences are not fully understood. Understanding the mechanisms that maintain loss of control eating is crucial to advance treatments that interrupt these processes. Affect regulation models of loss of control eating hypothesize that negative emotions trigger loss of control eating, and that loss of control eating is negatively reinforced because it temporarily decreases negative affect. Several variations on this basic affect regulation model have been proposed, including theories suggesting that negative affect decreases during loss of control eating rather than afterwards (escape theory), and that loss of control eating replaces one negative emotion with another that is less aversive (trade-off theory). Experience sampling designs that measure negative affect and eating behavior multiple times per day are optimally suited to examining the nuanced predictions of these affect regulation models in people’s everyday lives. This paper critically reviews experience sampling studies examining associations between negative affect and loss of control eating, and discusses the implications for different affect regulation models of loss of control eating. The review concludes by proposing an expanded affect-focused model of loss of control eating that incorporates trait-level individual differences and momentary biological and environmental variables to guide future research. Clinical implications and recommendations are discussed.